Understanding the consequences of sea level rise: the ecological implications of losing intertidal habitat. Issue 3 (3rd July 2022) - Rullens, Vera; Mangan, Stephanie; Stephenson, Fabrice; Clark, Dana E.; Bulmer, Richard H.; Berthelsen, Anna; Crawshaw, Josie; Gladstone-Gallagher, Rebecca V.; Thomas, Sam; Ellis, Joanne I.; Pilditch, Conrad A.
ABSTRACT: Sea level rise (SLR) has been described as one of the greatest potential causes of ecosystem disruption, putting many coastal areas at risk of irreversible changes. However, the loss of intertidal areas from SLR and the associated ecological and social repercussions receive little attention. Within estuaries, extensive intertidal areas harbour a variety of habitats and communities and represent hotspots of ecosystem functions. Any changes to their distribution or extent are likely to have far reaching implications. Here we summarise the ecological consequences of a reduction in intertidal area from increasing SLR, and the implications for people, management and planning. To facilitate this discussion, changes in the occurrence and abundance of two ecologically and culturally important intertidal shellfish species ( Austrovenus stutchburyi and Macomona liliana ) were modelled under different SLR scenarios for Tauranga Harbour, Aotearoa New Zealand. We highlight how the squeezing of intertidal areas will likely alter the distribution and extent of key habitats and communities, and discuss the implications for coastal food webs, ecosystem functioning and service provision. Pre-emptive planning and adaptive management are needed that incorporate ecological losses in risk assessments and focuses on pro-active solutions to increase resilience to the effects of SLR.